Faktor-Faktor Yang Mempengaruhi Kinerja Organisasi Bawaslu Republik Indonesia - Junaidi, Junaidi; Putra, Rino Dwi; Marantika, Abshor (Dinasti Review, 2024)
This research examines the factors that influence the performance of Bawaslu RI, namely using organizational culture variables, change management and information system success. This research uses descriptive analysis and the Structural Equation Modeling (SEM)-Lisrel statistical method. Data was collected from questionnaires distributed and returned from 325 Bawaslu members in Indonesia as respondents. The results of the study show that organizational culture, change management and the success of information systems have a positive and significant effect on the performance of Bawaslu RI.